Urban neighbourhood unemployment history and depressive symptoms over time among late middle age and older adults. Issue 2 (22nd August 2012) - Wight, Richard G; Aneshensel, Carol S; Barrett, Christopher; Ko, Michelle; Chodosh, Joshua; Karlamangla, Arun S
Abstract : Background: Little is known about how a neighbourhood's unemployment history may set the stage for depressive symptomatology. This study examines the effects of urban neighbourhood unemployment history on current depressive symptoms and subsequent symptom trajectories among residentially stable late middle age and older adults. Contingent effects between neighbourhood unemployment and individual-level employment status (ie, cross-level interactions) are also assessed. Methods: Individual-level survey data are from four waves (2000, 2002, 2004 and 2006) of the original cohort of the nationally representative US Health and Retirement Study. Neighbourhoods are operationalised with US Census tracts for which historical average proportion unemployed between 1990 and 2000 and change in proportion unemployed between 1990 and 2000 are used to characterise the neighbourhood's unemployment history. Hierarchical linear regressions estimate three-level (time, individual and neighbourhood) growth models. Results: Symptoms in 2000 are highest among those residing in neighbourhoods characterised by high historical average unemployment beginning in 1990 and increasing unemployment between 1990 and 2000, net of a wide range of socio-demographic controls including individual-level employment status. These neighbourhood unemployment effects are not contingent upon individual-level employment status in 2000. 6-year trajectories of depressive symptoms decrease over time on average but are not significantly influenced by the neighbourhood's unemployment history. Conclusions: Given the current US recession, future studies that do not consider historical employment conditions may underestimate the mental health impact of urban neighbourhood context. The findings suggest that exposure to neighbourhood unemployment earlier in life may be consequential to mental health later in life.